Role of patch testing in facial contact dermatitis: A cross-sectional study from central India - Hitesh Yadav; Satyaki Ganguly; Ajeet Singh (Wolters Kluwer Medknow Publications, 2024)
Background: Facial contact dermatitis is an emerging skin disorder due to the use of a large array of materials over the face. It leads to psychological distress in patients, impacting their quality of life. Most of the allergens applied over the face vary as per cosmetic or herbal products' availability, usage, or religious practices. Identifying and discontinuing the implicated allergens will lead to a better prognosis and reduced morbidity in clinical practice. Objectives: To determine the frequency of different allergens responsible for causing facial contact dermatitis, in an urban part of central India, using patch test with the help of Indian standard and cosmetic series. Materials and Methods: All suspected patients (>18 years) of facial contact dermatitis visiting the outpatient department of dermatology were patch tested with both Indian standard and cosmetic series. Results: Out of 38/58 patch-test-positive patients, 71.06% were females, and 28.94% were males. Most patch-test-positive females were housewives. The most common allergens implicated were thiomersal (17.24%), followed by fragrance mix (15.51%), and paraphenylene diamine (12.06%). Conclusion: In our study, forehead and malar areas were most commonly involved indicating fairness creams and perfumes as the important contributors to facial contact dermatitis. Antigen batteries need to be updated with changing social and cultural trends, as many with a consistent history of aggravation with some products tested negative in patch tests.